FIRST WORLD WAR ISSUE IN GEORGIAN LITERATURE - Chogovadze, Lela (Journal of Learning on History and Social Sciences, 2024)
General Background: The First World War (1914–1918) significantly reshaped global political landscapes, dismantling monarchies and empires and giving rise to new states, including Georgia's First Democratic Republic. Specific Background: During this period, Georgian poets, notably Titian Tabidze, expressed strong patriotic sentiments, seeing hope in war as a means to revive Georgia. His essay, War Theme in Georgian Writing (1915), reflects the belief that war, while destructive, could defeat evil and death, and lead to national rebirth. Knowledge Gap: There is limited scholarly analysis on how Georgian writers, particularly Symbolists like Tabidze, engaged with themes of war and national identity, especially in comparison to pacifist movements of the time. Aims: This study aims to explore Tabidze's pro-war stance in Georgian literature and its connection to the patriotic ideal of "glorious death over shameful life," contrasting it with pacifist writers like Herman Hesse and contemporaries who rejected war's necessity. Results: Tabidze’s essay reveals a poetic vision of war as a vehicle for national resurrection, rooted in heroic ideals. He laments that only a few Georgian poets, such as Vazha-Pshavela and Kote Makashvili, responded to the war theme in literature. Novelty: This work offers a fresh perspective on Georgian literature during WWI by highlighting Tabidze’s symbolism and pro-war idealism, often overlooked in broader studies of war literature. Implications: Understanding Tabidze's stance provides deeper insights into the interplay of war, national identity, and literature in Georgia, contributing to a more nuanced view of how small nations engaged with the broader global conflicts of the 20th century.